Cold-blooded vertebrates evolved regulatory B cells to participate in inflammatory diseases - Jie Wang; Wen-Jing Dong; Tian-Tian Tian; Chang-Song Wu; Xiang-Yang Zhang; Ya-Zhen Hu; Yi-Ru Pan; Xue-Qing Han; Jun Li; Carolina Tafalla; Yong-An Zhang; Xu-Jie Zhang (Cell Communication and Signaling)
Abstract Background Regulatory B cell (Breg), known for its immunosuppressive properties through the provision of IL-10, plays a critical role in the control of inflammatory diseases. Although Breg has been discovered for over two decades in mammals, its existence in non-mammalian vertebrates remains unclear. Here, we aimed to explore the differentiation mechanism and functional profiles of teleost CD25L+ Breg to gain insights into the origin and evolution of Breg. Methods Flow cytometry, RNA-seq, qPCR, morphological analysis, immunoblotting, immunofluorescence, recombinant IL-35 stimulation, cell co-culture in Transwell system were performed to reveal the phenotypic features, differentiation mechanism and suppressive functions of teleost CD25L+ Breg. To elucidate the immunoregulatory role of CD25L+ Breg in vivo, bacterial infection and inflammatory bowel disease (IBD) models were established in teleost fish. Systemic and local inflammatory responses were assessed by flow cytometry, immunofluorescence, histological analysis, and cytokine measurements. Results Phenotypically, we identified a unique IgM+CD25L+ B cell subset, termed CD25L+ B cells, characterized by their capacity to produce IL-10 and IL-12p35 in a cold-blooded vertebrate, the grass carp. Mechanistically, IL-35 stimulation induced the differentiation of CD25L− B cells into CD25L+ B cells, promoting the production of IL-35 and IL-10 via STAT3 activation. Functionally, teleost CD25L+ B cells served as a conventional Breg subtype that exerted its immunosuppressive functions on effector T cells and neutrophils via cell contact or cytokine delivery. Upon bacterial infection, CD25L+ Breg increased earlier than CD25L+ Treg and produced IL-10. In a 2,4,6-trinitrobenzene sulfonic acid (TNBS)-induced IBD model, Breg frequency and IL-10 levels increased significantly during IBD remission, and Breg adoptive transfer could prevent IBD development and contribute to intestinal tissue repair. Conclusions These novel findings reveal that fish have evolved Breg with specialized anti-inflammatory functions, providing evolutionary insights into the phylogenetic origin and functional conservation of Breg from fish to mammals.